Economic Development Strategies - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1995)
This paper provides a guide to economic development policies for local government managers. Local economic development policies today include not only tax subsidies for branch plants, but also job training to provide workers to businesses, advice and support services for potential entrepreneurs, and extension services to help businesses modernize and export. To help local government managers, this paper suggests a number of guiding principles, including: local economic development should be pursued cooperatively across the local labor market; economic development programs should consider the quality of jobs created; tax subsidies are expensive per job created; development subsidies are more effective if the subsidy is frontloaded; high unemployment areas should be more aggressive than low unemployment areas in promoting job growth; many economic development services can be cheaply evaluated by business surveys.
Additional information: A revised version of this paper appears as "Strategies for Economic Development" in J.R. Aronson and E. Schwartz, eds. 1996. Management Policies in Local government Finance (4th Ed.). Washington, DC: International City/County Management Association, pp. 287-312.
Keywords: J0; O0; 330; local; economic; development; Bartik